4^13 / 3^-5

1 answer

To simplify the expression, we need to use the properties of exponents.

Recall that when you divide two powers with the same base, you subtract their exponents.

So, 4^13/3^-5 is equivalent to (4^13) * (3^5), since dividing by a negative number is equivalent to multiplying by its reciprocal.

Now, let's simplify each term.
4^13 = (2^2)^13 = 2^26, using the property (a^b)^c = a^(b*c).

3^5 = 3 * 3^4 = 3 * (3^2)^2 = 3 * 9^2 = 3 * 81 = 243.

Therefore, 4^13/3^-5 simplifies to (2^26) * 243.

To calculate this value, you would multiply 2^26 by 243.